2022
DOI: 10.3390/pathogens11050587
|View full text |Cite
|
Sign up to set email alerts
|

Scratching the Itch: Updated Perspectives on the Schistosomes Responsible for Swimmer’s Itch around the World

Abstract: Although most studies of digenetic trematodes of the family Schistosomatidae dwell on representatives causing human schistosomiasis, the majority of the 130 identified species of schistosomes infect birds or non-human mammals. The cercariae of many of these species can cause swimmer’s itch when they penetrate human skin. Recent years have witnessed a dramatic increase in our understanding of schistosome diversity, now encompassing 17 genera with eight more lineages awaiting description. Collectively, schistoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 173 publications
(214 reference statements)
0
17
0
Order By: Relevance
“…McPhail et al [5] state that Planorbella have been less frequently included in snail surveys targeting schistosome discovery, and this may especially be the case where other avian schistosome species were already implicated in swimmer's itch or identified as the dominant species [6,7]. It is also possible that since some schistosome species are discovered in association with a swimmer's itch outbreak [3], the apparently diminished capacity of ASC to cause swimmer's itch has helped it evade detection. Outside of already understood swimmer's itch situations, Planorbella are among the most surveyed of all snails for trematodes, because of their geographic range, abundance, and frequent role as host for a high diversity of trematodes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…McPhail et al [5] state that Planorbella have been less frequently included in snail surveys targeting schistosome discovery, and this may especially be the case where other avian schistosome species were already implicated in swimmer's itch or identified as the dominant species [6,7]. It is also possible that since some schistosome species are discovered in association with a swimmer's itch outbreak [3], the apparently diminished capacity of ASC to cause swimmer's itch has helped it evade detection. Outside of already understood swimmer's itch situations, Planorbella are among the most surveyed of all snails for trematodes, because of their geographic range, abundance, and frequent role as host for a high diversity of trematodes.…”
Section: Discussionmentioning
confidence: 99%
“…Cercariae of avian schistosomes were first described in 1928 as the causative agents of an irritating condition known as cercarial dermatitis, or swimmer's itch, on Douglas Lake, Michigan [1]. Nearly 100 avian schistosome species have been identified around the globe, infecting snails of many different families, including Planorbidae [2,3]. Many planorbid snail genera have been found to be hosts to avian schistosomes, but there were no verified accounts of avian schistosomes in the genus Planorbella (Helisoma) until recently [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Its last reported presence in the United Kingdom was over 50 years ago, some 175 km further south, despite the more recent presence and study of avian schistosomatids elsewhere (Brant & Loker, 2009; Horák & Kolářová, 2011). Indeed, relatively little is known about this trematode and its natural history (Loker et al , 2022). For example, a recent molecular epidemiological study from one of the major recreational lakes in Poland has suggested the presence of a cryptic Bilharziella sister species, which is not surprising given the general lack of targeted surveillance for this trematode (Stanicka et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…First detected in the United Kingdom as emergent cercariae from the great ram's horn snail, Planorbarius corneus , in Roath Park Lake, Cardiff by Iles (1959), its last formal report was by Khan (1961), again as emergent cercariae from P. corneus from Lake Meadows Park, Billericay. Other avian schistosomatids, particularly those within the genus Trichobilharzia , are assumed to be primarily responsible for HCD in the United Kingdom (Lawton et al , 2014), across Europe (Soldánová et al , 2013; Żbikowska & Marszewska, 2018; Juhász et al, 2022) and elsewhere (Loker et al , 2022), overshadowing any B. polonica incrimination(s). From a phylogenetic perspective, B. polonica is basal to a diverse clade of avian schistosomatids that includes the species-rich genus Trichobilharzia ; the latter genus continues to expand upon increased populational sampling as novel genetic variants are encountered (Loker et al , 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation